(untitled) (Journal of Organizational Psychology, 2023)
Research has demonstrated that diverse teams perform better and are more creative and innovative. As such, many firms in industry have established DEI programs, especially those where forward-thinking design cognition are competitive advantages. These efforts correspond with a global talent and worker shortage and align with the realization that neurodiverse populations are eight times as likely to be unemployed, while most actively desire and seek work opportunities. The technology sector has been the first to consistently identify, build, and promote programs supporting the neurodiverse population, leveraging a largely untapped resource. With an estimated 15-20% of the global population considered to be neurodiverse, greater attention is being paid to the different needs and skills of this growing and diverse. To promote a potential competitive advantage, and address the needs of a neurodiverse workforce, certain firms are adopting biopsychosocial interventions in the workplace, including integration of behavioral education, redesigning hiring, resource training for managers, and environmental adaptations.